Keeping the water flowing : understanding the role of institutions, incentives, economics, and entrepreneurship in ensuring access and optimising utilisation of water / editors, Barun Mitra, Kendra Okonski, Mohit Satyanand. - Mitra, Barun S.; Okonski, Kendra; Satyanand, Mohit (Academic Foundation, 2007)
Contributed articles chiefly with reference to India; includes articles on water resources development in various countries of the world including India.